Improving upper extremity function in chronic stroke using occupational therapy task-oriented approach - Pongtham, Phonprapai; Chingchit, Waranya; P Dhippayom, Jananya (Journal of Associated Medical Sciences, 2021)
Background: Recovery of upper extremity function in chronic stroke requires functional rehabilitation. Objectives: The objective of this study was to investigate the effects of task-oriented occupational therapy on the upper extremity function of chronic stroke clients. Materials and methods: Twenty participants were selected for the study, which was carried out through purposeful sampling process. The participants were then divided into two groups: the intervention and the control groups. Both groups were given a conventional rehabilitation program. The intervention group was also provided with occupational therapy task-oriented training within the duration of 6 weeks, with the consistency of 3 sessions a week, and 1 hour each session. The training program was individually designed based on an analysis of the three most important activities identified by the participants from the Canadian Occupational Performance Measure (COPM). Each training session consisted of task-oriented training (75%) and supplementary exercise (25%). The Functional Test of the Hemiparetic Upper Extremity-Thai version (FTHUE-Thai Version) and COPM were used as outcome measurements before and after the training programs. Results: The FTHUE-Thai version study showed that the intervention group had significant improvement in the function of paretic upper extremity (p<0.05). The COPM’s report found a dramatical change in performance and satisfaction of the intervention group after the training program (p<0.05). These changes were also significantly different when compared between groups (p<0.05). Conclusion: This study indicated the effect of occupational therapy task-oriented training based on client-centered approach on improving functions of paretic upper extremities, occupational performance, and satisfaction in people with chronic stroke.